Decoding Niobium Carbide MXene Dual-Functional Photoactive Cathode in Photoenhanced Hybrid Zinc-Ion Capacitor - Azadmanjiri, Jalal; Regner, Jakub; Sturala, Jiri; Sofer, Zdeněk (ACS materials letters, 2024)
The coupling of energy harvesting and energy storage discrete modules in a single architecture as a "two-in-one" concept is significant in off-grid energy storage devices. This approach can decrease the device size and the loss of energy transmission in common integrated energy harvesting and storage systems. This work systematically investigates the photoactive characteristics of niobium carbide MXene, Nb2CTx, in a photoenhanced hybrid zinc-ion capacitor (P-ZIC). The unique configuration of the Nb2CTx photoactive cathode absorbs light to charge the capacitor and enables it to operate continuously in the light-powered mode. The Nb2CTx-based P-ZIC shows a photodriven capacitance enhancement of over 60% at the scan rate of 10 mV s-1 under 50 mW cm-2 illumination with 435 nm wavelength. Furthermore, a photoenhanced specific capacitance of ∼27 F g-1, an impressive photocharging voltage response of 1.0 V, and capacitance retention of ∼85% (over 3000 cycles) are obtained.